Constraining gluon distributions in nuclei using dijets in proton-proton and proton-lead collisions at $\sqrt{s_{_NN}} =$ 5.02 TeV - CMS collaboration (2298 authors) (2018)
The pseudorapidity distributions of dijets as functions of their average transverse momentum (pTave) are measured in proton-lead (pPb) and proton-proton (pp) collisions. The data samples were collected by the CMS experiment at the CERN LHC, at a nucleon-nucleon center-of-mass energy of 5.02 TeV. A significant modification of the pPb spectra with respect to the pp spectra is observed in all pTave intervals investigated. The ratios of the pPb and pp distributions are compared to next-to-leading order perturbative quantum chromodynamics calculations with unbound nucleon and nuclear parton distribution functions (PDFs). These results give the first evidence that the gluon PDF at large Bjorken x in lead ions is strongly suppressed with respect to the PDF in unbound nucleons.